DETERMINANTS OF CAPITAL STRUCTURE OF LEASING COMPANIES IN PAKISTAN - Andaleeb, Shazila; Abbasi, Muneer Ahmed; Naqvi, Syed Iqbal Hussain; Ali, Shahan (Archives of Business Research, 2018)
The purpose of the research is to study the determinants of capital structure of leasing companies in Pakistan listed on Karachi Stock Exchange during the period of 2006-2015. In this study data was collected from at Karachi Stock Exchange .In this study experts and professional can break down whether the practices in the exact corporate world are identified with the hypothetical perspectives of capital structure. This part of research  provide us a review of the theoretical framework literature on capital structure whether the significance of leverage benefits  and its cost will run the managers to make decisions based on leverage of capital structure and its market opportunities for guiding them to various debts and equity issues? Do managers have leverage targets change over the time or they adjust equity debt ratio continuously or they don’t have targeted leverage to maintain? The unit of investigation is the recorded firms in PSX record with the negligible specialists' impedance. Study defines adjusted panel information which was gathered from secondary sources. The study applies econometrics displaying utilizing both single condition and diminishes condition models for panel information. Panel econometric procedures specifically pooled common minimum squares, settled impacts, and irregular impacts were utilized to research the effect of capital structure on execution of finance related firms recorded on the Karachi Stock Exchange from 2006-2015